A SOCIAL SEMIOTIC ANALYSIS OF GENDER REPRESENTATION IN SELECTED KENYAN SECONDARY SCHOOL ENGLISH TEXTBOOKS - MUTUNE, FELLIS NTHAMBI (MksU Press, 2023)
The present study is a social semiotic analysis of gender representation in selected Kenyan secondary school English textbooks. Textbooks are a powerful instrument for creating social identities. As a result, how male and female genders are represented in textbooks can have a big impact on how students perceive men and women in society. As a result, eliminating gender biases in textbooks and, in turn, the curriculum, is an essential step in achieving equality in education, which is a fundamental objective of both Education for All and the Sustainable Development Goals. Reviews of textbooks indicate that minor concerns regarding gender roles and representations are obvious, despite efforts to address differences in the visibility, position, and perceived potential of males and females represented in textbooks. The objective of the present study is to identify how gender is depicted in English textbooks by first analysing linguistic signals. Second, the study explores how gender is represented in the visual signs. Third, the study assesses the social factors that underlie how gender is portrayed in the chosen secondary English textbooks from Kenya. Explanatory sequential research design was used in the study (Creswell & Plano Clark, 2011). Purposive approaches were used to sample four textbooks that were provided and approved by the Ministry of Education. The four textbooks are those used in Kenya's secondary schools to facilitate the teaching and study of English. Social semiotics theory, SFL theory, and Social construction of reality theory (Berger & Luckmann, 1991) served as the study's guiding principles. All of the genderrelated data was manually generated for each item. A document analysis guide derived from the model for analysing visual images by Kress and van Leeuwen (2006) and Systemic Functional linguistic framework by Halliday (2004, 1994) was employed in the analysis of quantitative data from the visual and linguistic signs in the four textbooks. A number of central outcomes emerged. From the analysis, first variations were noted in the number of males and females in both linguistic and visual signs. The findings revealed that males‘ images transcended the females‘ in the textbooks. More males were also portrayed playing the actor role and they were involved in more instances in both nontransactional and transactional actional processes, in addition to having more gazes towards the reader than the females. The linguistic analysis showed that males outnumbered the females in the theme and rheme position, in the relational, mental, material and verbal processes. On the analysis of the social contexts that underlie the representation of gender in visual and linguistic signs, it was revealed that in addition to unequal portrayals of both genders, gender stereotypical depictions were observed which may be interpreted as gender bias favoring males. Certainly, the analysis revealed that visuals and linguistic signs implicitly and explicitly represented males as superior to females. The study recommends that materials for English textbooks be created and chosen with gender concerns in mind. The Kenya Institute of Curriculum Development could begin a review and revision of the textbooks to ensure that there is a gender balance in the written and visual cues. The study is expected to advance our understanding of language and gender, language in the classroom, and applied linguistics.